PENGARUH MASSA ADSORBEN KULIT KAKAO (Theobroma cacao L.) DAN pH DALAM PENURUNAN CHEMICAL OXYGEN DEMAND (COD) LIMBAH PALM OIL MILL EFFLUENT (POME) - Akuri, Melan (Department of Chemistry - Universitas Bangka Belitung, 2025)
Cocoa shell (Theobroma cacao L.) is a plant waste that has not been widely utilized. Cocoa husk contains cellulose, hemicellulose, lignin, fat and crude fiber so that it can be used as an adsorbent to reduce COD levels in POME. POME is a brown liquid released from the factory which contains a lot of dissolved solids. COD is the total amount of oxygen required to chemically or biologically oxidize organic matter to CO₂ and H₂O. This study aims to determine the characteristics of cocoa pods and to determine the mass of the adsorbent and the optimum pH in reducing COD in POME. Cocoa shells were dried in an oven for 24 hours, then mashed and sieved using a 100 mesh size. Then activated using 0.6 M nitric acid with a ratio of 1:10. Cocoa husk adsorbent was tested for moisture and ash content, which were 10.40% and 4.08%, and characterized using SAA obtained a surface area 0.547 m²/g. Furthermore, the determination of the optimum mass and pH using the COD test method with closed reflux titrimetrically. The optimum mass of the adsorbent is 1 gram and the pH is pH 4 with an allowance for a decrease of 40%; 96%, the COD content is 153,187.2 mg/L; 8,510.4 mg/L with an adsorption capacity of 5,106.24 mg/g:12,340.08 mg/g.